Outsourcing and Offshoring - Franco, Mário (IntechOpen, 2021)
Outsourcing and offshoring are typically viewed as phenomena allowing competitive advantages for organizations, but some studies have not included the risks, benefits, and challenges of these types of strategies. As such, this book fills this gap by combining several studies from different perspectives. The chapters follow several approaches and applications that researchers explore in different contexts. This book adds to the body of knowledge in outsourcing and offshoring areas and shows how these strategies can stimulate organizations' development in various countries and regions worldwide.